Striving for Removing Stammer In The King's Speech Movie By Tom Hooper (2010): An Individual Psychological Approach - PRABOWO, DADANG (2012)
The problem of this study is to reveal how is striving for removing stammer in major character. The objective of the study is to analyze the major character in The King's Speech movie based on Individual Psychological Approach. The study is a literary study, which can be categorized into a descriptive qualitative study. The object of this study is The King's Speech movie. The data sources are primary and secondary data sources. The primary data source is the movie The King's Speech script and the secondary data are related to the primary data that support the analysis such as some books of psychology and website related to the research. The method used for collecting data is library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the writer concludes that the problem faced by the major character is strived to go out of his condition, it causes the writer to use individual psychological perspective such as: Inferiority Feeling, Striving for Superiority, Fictional Finalism, Style of Life, Social Interest, Creative Power. By using this method, it is known how Duke of York as the major character can solve his problem.